2004
DOI: 10.1038/nm1134
|View full text |Cite
|
Sign up to set email alerts
|

Specific peptide interference reveals BCL6 transcriptional and oncogenic mechanisms in B-cell lymphoma cells

Abstract: The BTB/POZ transcriptional repressor and candidate oncogene BCL6 is frequently misregulated in B-cell lymphomas. The interface through which the BCL6 BTB domain mediates recruitment of the SMRT, NCoR and BCoR corepressors was recently identified. To determine the contribution of this interface to BCL6 transcriptional and biological properties, we generated a peptide that specifically binds BCL6 and blocks corepressor recruitment in vivo. This inhibitor disrupts BCL6-mediated repression and establishment of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
376
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(384 citation statements)
references
References 30 publications
8
376
0
Order By: Relevance
“…In the BCL6 locus, the orange triangle indicates the exon 1 BCL6 binding sites studied in panel A. Opaque masking windows represent the cutoff defined as 2.5 times the standard deviation above the average relative enrichment on the entire array. (15,35). Our CtBP siRNA experiment revealed that CtBP also contributes to repression of CCL3 (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In the BCL6 locus, the orange triangle indicates the exon 1 BCL6 binding sites studied in panel A. Opaque masking windows represent the cutoff defined as 2.5 times the standard deviation above the average relative enrichment on the entire array. (15,35). Our CtBP siRNA experiment revealed that CtBP also contributes to repression of CCL3 (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…To address this issue, we evaluated the response of the endogenous BCL6 gene to the POZ lateral groove corepressor blocking peptide, BPI. We have previously shown that BPI treatment can derepress a number of BCL6 target genes in mature B cell lines (35). BCL6-positive SUDHL6 cells were treated with BPI and assayed for changes in BCL6 expression by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests the possibility of disrupting the interaction between c-Myb and CBP/ p300 as an approach to targeting c-Myb. This may be achievable using small molecules or peptides, because disruption of protein-protein interactions with such agents is now considered a feasible strategy for drug development (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…These different co-repressor complexes appear to suppress distinct gene sets, perhaps mediating different activities of BCL6 in various immune cells. This notion has been in part supported by studies using inhibitors that selectively disrupt the co-repressors binding to the BCL6 BTB (BR-C, ttk and bab) domain [14,15]. However, the link between the transcriptional mechanisms of action of BCL6 with its biological actions in the immune system remains to be further characterized.…”
mentioning
confidence: 99%